THE USE OF LEXICAL REPETITION IN THE WRITTEN MONUMENT OF KULTEGIN (Scientific journal of the Fergana State University, 2026)
The article examines the use of lexical repetition found in ancient inscriptions, particularly in the Kultegin inscription. Examples of parallel syntactic constructions in the epic text are analyzed. Literature, as the spiritual heritage of a nation, has historically evolved through oral creativity. In particular, works of the epic genre, such as epics and legends, serve as artistic expressions of people’s thinking, traditions, and historical life. The article highlights the worldview, moral and ethical values, and aesthetic taste of the Uzbek people based on works created in ancient times. This study provides insight into national mentality and history through folk oral creativity. The lexical repetitions found in the inscriptions reveal the linguistic system, grammatical structure, and artistic worldview of that period.